The influence of futsal players` initial physical condition on the occurrence of injuries - Rebelo, M.; Marques, C.; Crisóstomo, R.; Batista, M.; Paulo, R.; Rocha, J.; Serrano, J. (International Journal of Sports Medicine, 2024)
Although there are some studies that have linked fitness parameters and sports injuries, the literature remains controversial. The aim of the study was to prospectively analyze the influence of initial physical condition parameters on the development of injury in the first three months of the sports season in futsal players. A total of 68 players (24.26±4.63 years old) were assessed before the start of the sports season in relation to certain physical condition parameters, such as body composition (bioimpedance), lower limb power (countermovement jump, CMJ) and muscle strength (isokinetic dynamometer). The injured players showed significantly worse initial performance in the CMJ compared to the uninjured players (p<0.001). There were no significant differences between groups in body composition and muscle strength. Lower power values were associated with a higher risk of injury in the first few months of the sports season (OR=0.92; 95% CI=0.88-0.99). Muscle power was an independent predictor of injury in the first few months of the sports season in futsal players, indicating that improving players` physical condition could help reduce the number of injuries.